The teaching learning process of english at vocation high school 3 klaten 2012 an ethnography study in vocational school 3 klaten - Suyamto, Suyamto; , Prof. Dr. Endang Fauziati, M. Hum; , Dra. Siti Zuhriyah Ariatmi, M. Hum (2014)
The study aims to enhance the learning achievement of English especially at Vocational High School 3 Klaten ,by improving students' ability to solve English skill's problem through Teaching Learning Process of English effectively . The research problem of the study is how the teaching learning process of English at Vocational High School 3 Klaten. The objectives of the study reveal briefly of Teaching Learning Process of English at Vocational High School 3 Klaten in which encompasses syllabus, learning objective, instructional material, teaching design, evaluation and strength and weakness of English Teaching. The research was an ethnography study. The efforts of study overview national - functional syllabus which categorized into novice level, elementary level, and intermediate level. The learning objective are general and specific learning out come. The instructional material is devided into printed, audio and visual material. The teacher's roles are facilitator, observer, organizer and explainer. The student's roles are processor, performer and listener. The classroom procedure is three patterns namely : BKOF - MOT - JCOT - TCOT - BKOF - MOT - JCOT and BKOF - MOT - JCOT. The classroom activities are advance organizer, classroom practice, question and answer, silent reading, reading aloud, role play and comprehension. The media are grouped into two forms. The first is printed media such as picture, letter. The second is printed media for instance tape recorder and compact disk. The evaluation describes evaluation model and kind of evaluation. The evaluation models are completion task, close procedural text and multiple choice. The kind of evaluation involves formative, sub summative, mid semester and summative / last semester. There are strength and weakness among teaching learning process of English at Vocational High School 3 Klaten. Departing with the finding, discussion, conclusion and implication, the researcher suggests for English teacher to encourage student, engagement in the classroom, the application of diverse methods and techniques are obviously required in teaching English. The researcher also recommends for next writer to expand the study in other research field.